Community Disaster Risk Assessment in Arusha City, Tanzania - Hambati, Herbert (Tanzania Journal for Population studies and Development, 2017)
Urban population growth has demonstrated synergetic relationship with the growth of informal settlements and disasters, especially in developing countries. The increase in the density of people in informal settlements in Tanzania has accelerated their vulnerability to disaster risks. This study employs Community Participatory Disaster Risk and Vulnerability Assessment (PDRVA) to analyse vulnerability to disasters in informal settlements in Arusha city, Tanzania. The results show that a plethora of factors—human, physical, social, and economic—interact in a complex non-linear way to shape vulnerability to disasters in informal settlements in the city. Indigenous and western knowledge in the settlements used to cope with environmental hazards hold a great potential in shifting community responses to long-term considerations. The study recommends that measures and strategies aimed at reducing disaster risks should address the whole set of issues leading to poverty and disparities within the community.